Habitat associations of Meretrix spp. in a mangrove coastal area of North Sumatra, Indonesia - SHALVIA JARI REFOMIA SIAHAAN; NORMA AFIATI; MUHAMMAD HELMI (Society for Indonesian Biodiversity, 2026)
Abstract. Siahaan SJR, Afiati N, Helmi M. 2026. Habitat associations of Meretrix spp. in a mangrove coastal area of North Sumatra, Indonesia. Biodiversitas 27 (6): d270609. https://doi.org/10.13057/biodiv/d270609. The hard clams of the genus Meretrix are ecologically and economically important bivalves in tropical coastal ecosystems, yet information on their habitat associations in North Sumatra remains limited. This study examined the estimated density, spatial distribution, and habitat associations of Meretrix meretrix, M. lusoria, and M. astricta in the mangrove coastal area of Sei Nagalawan, Serdang Bedagai Regency, North Sumatra, Indonesia. Sampling was conducted at 30 intertidal stations during low tide. Sediment characteristics and water-quality variables were measured at each station to characterize local habitat conditions. Spatial patterns were visualized using GIS-based Spline interpolation, whereas Principal Component Analysis (PCA) was applied to summarize environmental gradients across the study area. A total of 517 molluscan individuals representing 12 taxa were recorded. Meretrix meretrix was the dominant species, accounting for 55.1% of the total abundance, followed by M. lusoria. The molluscan assemblage was characterized by low diversity (H′: 0.786), high evenness (E: 0.820), and moderate dominance (C: 0.516). Morisita’s index indicated clumped distribution patterns for all recorded Meretrix species. Estimated density ranged from 2 to 17 ind m⁻². PCA indicated that environmental variation among sampling stations was associated primarily with sediment texture and secondarily with water-quality conditions. Stations with higher Meretrix occurrence were generally associated with coarser sediments, whereas lower occurrences were recorded at stations containing higher proportions of fine sediments. Spatial interpolation revealed heterogeneous density patterns across the study area, with a root mean square error (RMSE) of 3.58. Differences in Meretrix occurrence among stations reflected variation in local habitat conditions across the study area. These findings provide baseline ecological information for future monitoring and management of mangrove-associated bivalve resources in North Sumatra, Indonesia.